Applicability of evaluation instruments and techniques according to the competence model of MEDUCA to assess the speaking area of the english program at Junior High School Level at I.P.T. Arnulfo Arias Madrid High School. David, Chiriquí 2013 - Aizpurúa, Ayleen; Henríquez, Cretel (David, Panamá : UDELAS, 2013)
This research has an importan goal, it consists in achieve a good use of the evaluation instruments for teaching at junior school. Also, it contains some information of the defferent types of evaluation instruments and ways how to use them. Summarizing, this is a good tool in order to enjoy the process of english learning as a second language.
INDEX Chart index Graphic index Introduction CHAPTER I: RESEARCG PROBLEM CHAPTER II: THEORICAL FRAMEWORK 2.1. The function of evaluation for the compentecy model 2.1.1. Competence concept 2.1.2. Competency model 2.1.3. Process of competence acquisition 2.1.4. Function of evaluation 2.2. The different evaluation instruments for the speaking area and topics of Junior School level 2.2.1. Types of evaluation 2.2.1.1. According to the purpose and function 2.2.1.2. According to the extension 2.2.1.3. According to the agent assessors 2.2.1.4. According to the moment of evaluation 2.2.2. Evaluaation instruments 2.2.2.1. Learnign evaluation 2.2.2.2. Evaluation of the effects 2.2.3. English speaking area 2.2.4. Topics of Junior School level 2.3. The english teacher tries new alternatives and show the importance of the different kind of evaluation 2.3.1. English teacher role 2.3.2. New alternative 2.3.3. Importance of the kind of evaluations 2.3.4. Evaluation activities 2.4. Role of the teachers and students according to the evaluation instruments related to competence model 2.4.1. Role of students 2.4.2. School environment 2.4.3. Techniques of evaluation CHAPTER III: METHODOLOGICAL FRAMEWORK CHAPTERIV: ANALYSIS OF THE RESULTS Conclusions Recommendations Bibliography Annex 1
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; ENGLISH -- TESIS DE LICENCIATURA -- EVALUATION; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLES; I.P.T. ARNULFO ARIAS MADRID HIGH SCHOOL